Trachoma, Anti-Pgp3 Serology, and Ocular Chlamydia trachomatis Infection in Papua New Guinea. (22nd January 2020) - Macleod, Colin K; Butcher, Robert; Javati, Sarah; Gwyn, Sarah; Jonduo, Marinjho; Abdad, Mohammad Yazid; Roberts, Chrissy H; Keys, Drew; Koim, Samuel Peter; Ko, Robert; Garap, Jambi; Pahau, David; et al.
Abstract: Background: In Melanesia, the prevalence of trachomatous inflammation–follicular (TF) suggests that public health–level interventions against active trachoma are needed. However, the prevalence of trachomatous trichiasis is below the threshold for elimination as a public health problem and evidence of conjunctival infection with trachoma's causative organism ( Chlamydia trachomatis [CT]) is rare. Here, we examine the prevalence of ocular infection with CT and previous exposure to CT in three evaluation units (EUs) of Papua New Guinea. Methods: All individuals aged 1–9 years who were examined for clinical signs of trachoma in 3 Global Trachoma Mapping Project EUs were eligible to take part in this study (N = 3181). Conjunctival swabs were collected from 349 children with TF and tested by polymerase chain reaction to assess for ocular CT infection. Dried blood spots were collected from 2572 children and tested for anti-Pgp3 antibodies using a multiplex assay. Results: The proportion of children with TF who had CT infection was low across all 3 EUs (overall 2%). Anti-Pgp3 seroprevalence was 5.2% overall and there was no association between anti-Pgp3 antibody level and presence of TF. In 2 EUs, age-specific seroprevalence did not increase significantly with increasing age in the 1- to 9-year-old population. In the third EU, there was a statistically significant change with age but the overall seroprevalence and peak age-specific seroprevalence was very low. Conclusions: Based on these results, together with similar findings from the Solomon Islands and Vanuatu, the use of TF to guide antibiotic mass drug administration decisions in Melanesia should be reviewed. Abstract : In Papua New Guinea (PNG), prevalence of trachomatous trichiasis is very low. This study demonstrates that prevalence and transmission of ocular Chlamydia trachomatis, a driver of progressive trachomatous disease, is much lower in PNG than in other settings with similar active trachoma prevalence.